PENGARUH POSISI SERAT KACA (FIBERGLASS) YANG BERBEDA TERHADAP KEKUATAN FLEKSURAL FIBER REINFORCED ACRYLIC RESIN - Aprilia Dian Fatimina; Benni Benyamin; Helmi Fathurrahman (Faculty of Dentistry, Universitas Islam Sultan Agung, 2016)
Background: One of factor that increases the flexural strenght of fiberreinforced acrylic resin is a fiberglass position . Fiberglass is one of type that can be used in dentistry. The aim of this was to determine the influence of position of fiberglass to the flexural strenght of fiber reinforced acrylic resin.Method: This study was in vitro laboratory experimental. Samples was 16plate spesimens (65x10x2.5mm). The study group was divided into 4 group : 3 groups of fiber reinforced acrylic resin were given fiberglass at the upper, middle, and bottom side and 1 control group of resin acrylic without fiberglass. All of groups would be in the flexural strenght test with a three-point bending test using a universal testing machine.Result: Based on One Way ANOVA test showed that there were significantvalue 0.000 (p<0.05), it concluded that there were significant influencebetween all the groups. Based on the LSD Post Hoc test showed that therewere significant value between all of groups with fiberglass reinforced andcontrol group without fiberglass reinforced. Comparisson between the group that given fiberglass in a upper and middle side with the group that given in bottom side showed value of significant difference (p < 0.05).Conclusion: The result of study was concluded that there was an influenceon the position of fiberglass to flexural strenght of fiber reinforced acrylic resin